Reflecting human values in the digital age - Sellen, Abigail; Rogers, Yvonne; Harper, Richard; Rodden, Tom (Communications of the ACM, 2009)
HCI experts must broaden the field’s scope and adopt new methods to be useful in 21st-century sociotechnical environments.